PENGARUH PENYULUHAN KARIES GIGI DENGAN MEDIA MONTASE TERHADAP PENGETAHUAN SISWA KELAS IV DI SDN JAWA 5 KABUPATEN BANJAR - Rahmi, Sri Aulia; Amperawati, Metty; Ulfah, Rasuna; Kisworo Utami , Naning (Poltekkes Kemenkes Banjarmasin, 2025)
Indonesians have a proportion of oral problems of 57.6%, and only 10.2% receive services from dental professionals. The prevalence rate of dental caries in all age groups in Indonesia is 88.8% and Banjar Regency has a dental caries severity rate of 43.34%. Dental caries can be caused by a lack of public knowledge about oral health efforts. Lack of knowledge affects children's ability to maintain dental health. This research aims to determine the effect of dental caries counseling with montage media on the knowledge of fourth grade students at SDN Jawa 5 Banjar Regency. This research method uses a type of pseudo-experimental research with a research design using a control group pretest posttest design. The sample of this study used total sampling with a sample size of 58 people. The results of statistical tests obtained knowledge before counseling with montage media amounted to 6.87 and after counseling amounted to 11.53. Paired Sample T-Test results ρ-value 0.000 < α = 0.05 so Ho is rejected and Ha is accepted. The conclusion is that there is an effect of dental caries counseling with montage media on the knowledge of grade IV students at SDN Jawa 5 Banjar Regency. It is recommended that health workers, especially in the field of oral health, carry out promotive activities for students in these elementary schools, especially continuous counseling using interesting and not boring media to further increase student knowledge.